The Variability of Surface Ozone Concentration Over Different Localities of Delhi And the Correlation of It With the Emission of Precursor Gases Like Nox, Sox and the Amount Of Solar Radiation - Bashabi Gupta, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Atmosphere is a gaseous envelops hanging over the earth’s surface. It is composed of different types of gases mixed in a distinct proportion. Some of them are constant in their proportion, while others are variable in characters over space and time. Nitrogen, Oxygen, CO₂, Argon, Ozone, Water vapor, Neon, Hydrogen, Helium etc. is the some among them. Each of these gases is plying a prominent role in the structuring of the earth’s biosphere and vice versa. It is this distinct composition making the earth different from other planets and makes the life possible on it.